The TensorFlow workshop : a hands-on guide to building deep learning models from scratch using real-world datasets /: a hands-on guide to building deep learning models from scratch using real-world datasets. (2021) - Maddalone, Anthony; Moocarme, Matthew; So, Anthony
No abstract available